Biofilm formation by S.aureus on composite scaffolds – A qualitative and quantitative in vitro analysis. (2019) - Priya, G.; Anitha, R.; Akila, R.; Narendra Kumar, U.; Manjubala, I.
Abstract: Failure of implants is a serious concern in the orthopedic field, due to loosening of the parts or biofilm formation. This leads to secondary surgery increasing the cost for the patients. The analysis of the ability of the implants to be resistant to infection or susceptible to biofilm growth before implantation could minimize this issue. The aim of this study is to investigate the ability to form biofilm on composite scaffolds, made up of polymer and calcium phosphates. The growth and proliferation of the microorganisms was evaluated quantitatively for biofilm formation by MTT assay and viable cell count (VCC) by vortexing. The surface colony morphology of biofilm on scaffold was observed using scanning electron microscopy. Biofilm formation was significantly higher on BG5 (p<0.05) as measured by MTT assay. But no profound difference was observed by viable cell count. Colony morphology analysis also showed a dense layer of biofilm on BG5, whereas only microcolonies were formed on other samples. BG5 is relatively more susceptible to biofilm formation compared to other compositions. This study also highlights the use of MTT assay for effective quantification of biofilm in scaffolds.